2021
DOI: 10.1186/s41479-021-00083-w
|View full text |Cite
|
Sign up to set email alerts
|

The role of co-infections and secondary infections in patients with COVID-19

Abstract: Background It has been recognised for a considerable time-period, that viral respiratory infections predispose patients to bacterial infections, and that these co-infections have a worse outcome than either infection on its own. However, it is still unclear what exact roles co-infections and/or superinfections play in patients with COVID-19 infection. Main body This was an extensive review of the current literature regarding co-infections and super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
246
1
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(258 citation statements)
references
References 142 publications
(225 reference statements)
4
246
1
7
Order By: Relevance
“…In another systematic review of 101 cases of CAM, it was observed that 81% of the cases were from India and hyperglycemia at presentation was the predominant risk factor in 83% of the cases (15% had concomitant DKA), with history of corticisteroid treatment for COVID-19 in 76.3% [3] . While systemic steroids have been shown to offer survival benefit in COVID-19, their immunosuppressive action together with underlying diabetes and the complex cascade of SARS-CoV-2-induced immunological events, lead to an inflammatory state which might favour invasive fungal infections [ 1 , 18 ]. In the present series, both the patients had COVID-19 with uncontrolled diabetes and concomitant DKA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another systematic review of 101 cases of CAM, it was observed that 81% of the cases were from India and hyperglycemia at presentation was the predominant risk factor in 83% of the cases (15% had concomitant DKA), with history of corticisteroid treatment for COVID-19 in 76.3% [3] . While systemic steroids have been shown to offer survival benefit in COVID-19, their immunosuppressive action together with underlying diabetes and the complex cascade of SARS-CoV-2-induced immunological events, lead to an inflammatory state which might favour invasive fungal infections [ 1 , 18 ]. In the present series, both the patients had COVID-19 with uncontrolled diabetes and concomitant DKA.…”
Section: Discussionmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continues to be a major public health problem worldwide. Recent reports suggest an increased incidence of secondary bacterial and fungal infections in COVID-19 patients [1] . While COVID-19 associated pulmonary aspergillosis (CAPA) has been extensively discussed, other invasive fungal diseases such as candidemia, trichosporonosis, fusariosis, histoplasmosis, cryptococcosis, coccidioidomycosis and currently, COVID-19 associated mucormycosis (CAM) have also been reported [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Secondary infections that provide additional stress for an already imbalanced immune system may further amplify inflammation. Typically, hosts are already infected by one or more persistent viruses and the virus-virus interplay may contribute to aberrant innate immune signaling [196]. Lastly, aberrant inflammation is further promoted by ageing of the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…These secondary infections may further fuel the state of chronic inflammation, providing additional triggers to immune sensors. Incoming viral proteins may manipulate innate immune pathways, again leading to aberrant reactions, and thus eventually facilitate development of PAS [22,196]. Notably, acute infections often occur in hosts that are (acutely and/or latently) infected with multiple other viruses.…”
Section: Chronic Inflammation Induction By Non-persistent Virusesmentioning
confidence: 99%
“…Prompt treatment of sHLH with broad immunosuppressive or immunomodulatory therapies such as glucocorticoids, cyclosporine, intravenous gamma globulin, anti-IL-6 and anti-IL-1 agents, or chemotherapeutics is important for favorable outcomes. However, use of immunosuppressant therapy in COVID-19 patients must be done cautiously, as co-infections can occur with COVID-19, and such infections have been associated with severity of SARS-CoV-2 as well as poor outcomes [ 8 ].…”
Section: Introductionmentioning
confidence: 99%